Supervisi Pengembangan Mutu Pendidikan: Tinjauan Konsep Developmental Supervision Glickman - Nur Rahmi Sonia (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2022)
Currently, developmental models of supervision have dominated supervision thinking research throughout the world. But its importance were not well known by the implementer like supervisors and teachers and school principals particularly in developing countries. Therefore, this article aims to provide insight into understanding the essence of monitoring developments. The methodology or approach used in this paper uses a library research method or approach, while data collection is carried out by reviewing and/or exploring several journals, books, and documents (both printed and electronic) as well as data sources. and or other information deemed relevant to the study. The results of the study indicate that supervisors in carrying out have a collection of approaches in their implementation that adjust the characteristics of teachers appropriately. That way, the supervisor can determine a starting point for using supervisor orientation with individual teachers. Therefore, developmental supervision is based on three broad propositions, namely, first, based on varying backgrounds and experiences, teachers operate at different levels of professional development. Second, the ability and effectiveness of teachers are also different, so they need to be improved in different ways. Third, the long-term goal of supervision must be to increase the ability of every teacher and school to grow to a higher stage.